Designs for learning in museum contexts - Eva Insulander; Staffan Selander (Stockholm University Press, 2009)
This article presents a new theoretical and methodological way of studying museum visitors' involvement and meaning-making at a museum exhibition. Our approach draws predominantly on a design-theoretic and multimodal analysis of learning and communication. This approach is mainly concerned with a) the design aspects of learning resources; b) the learners' engagement and communication; c) their way of transforming given signs to produce (redesign) their own representations in relation to d) personal engagement as well as a specific areas of knowledge. Multimodality pays special attention to the interplay between different modes in communication. In the article, we use a design-theoretic, multimodal approach to analyse visitors' engagement. This is done by filming the visitors in pairs to see how they walk through the exhibition, where they stop, what they talk about and how their conversation develops. They are also given cameras so they can take photos of those parts of the exhibition they find especially interesting, Afterwards, the visitors are asked to draw a map of the exhibition and they are also interviewed. We also present a model of how to categorize forms of engagement.